(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Metals may be present in long-staple seeded cotton falling into the roller gin. Metal impurities damage the equipment during operation. In order to prevent this, w place a piece of magnet in the equipment that catches metal compounds. The seeded cotton falls into the pile drum through the securing roller. There, it is cleaned of small impurities and enters the working chamber through a chute.